MANAGING AND MARKETING OF THE PRODUCTS OF FRUIT TREE - REGION OF KORCA ALBANIA - Sosoli, Ilir (European Scientific Journal, ESJ, 2014)
Korca District is situated in southeastern Albania, in the Central Mountainous Region. Economically speaking, Korca used to be one of the most important centers in the region, in which trade of agricultural products with other countries took place. The main sectors of business include the agro-business sector, garments and tourism. Korca ranks second nationwide in terms of the size of the agricultural land, which makes agriculture the most important sector of its economy. Agricultural products account for 32 percent of all revenues. Great prospects are in store for the small and medium agro-business enterprises and consequently, for the size and relevance of the agricultural sector in the Korca District. During the last years the production of fruit tree has intensified greatly and this has put the farmers in front of new challenges for their activity. In this respect marketing has acquired a great emphasis, whose role is becoming even more important. This material aims to analyze some of the alternative marketing which can be used to gain a competitive advantage. The methodology of the study includes gathering secondary data and the study of literature in this field. The study ends with giving some conclusions to all the partners in the marketing channel in order to create a long-term relationship and survival in the competition.